Encapsulation of unique anionic carboxylic acid/water cluster chains into channels of a three-dimensional cationic framework - Tang, E.; Dai, Yu-Mei; Chen, Y.; Lang, Jian-Ping; Yao, Yuan-Gen; Weng, Ng-Seik (Elsevier, 2010)
The hydrothermal reactions of CuCl with 1,3-bis(4-pyridyl)propane (bpp), 1,3-benzenedicarboxylic acid (1,3-H(2)bdc), and KOH in water afforded {[Cu(8)Cl(4)(bpp)(8)][(1,3-Hbdc)(4)(H(2)O)(9.5)]}(n) (1). Single-crystal X-ray diffraction revealed that 1 has anionic [(1,3-Hbdc)(4)(H(2)O)(9.5)](n)(4n-) water cluster chains that are encapsulated into the 1D channels of a 3-D [Cu(8)Cl(4)(bpp)(8)](n)(4n+) cationic framework. The thermal and luminescent properties of 1 in the solid state were also investigated. (C) 2010 Elsevier BM. All rights reserved.